Pengaruh Disiplin Kerja, Lingkungan Kerja, dan Komunikasi Efektif Terhadap Loyalitas Kerja Karyawan Pada PT Sentong Sultan Keraton Majapahit Kota Kediri - Rahmadani, Dian Novi; Saputra, Beny Mahyudi; Murdiyanto, Edi (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the effect of work discipline, work environment, and effective communication on employee loyalty at PT. Sentong Sultan Keraton Majapahit in Kediri City. This research uses a quantitative associative approach with a survey method. The population consists of 35 employees, all of whom were selected as samples using the total sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS version 25. The results show that work discipline and work environment have a positive and significant effect on employee loyalty, while effective communication has a positive but not significant effect. Simultaneously, all three independent variables significantly influence employee loyalty, with a determination coefficient (R²) of 0.779, indicating that 77.9% of loyalty variation is explained by these factors. Therefore, this study concludes that consistent implementation of work discipline and the creation of a conducive work environment are key determinants of employee loyalty, while effective communication should be strengthened to optimize its role in maintaining harmonious workplace relationships.